(untitled) (American Journal of Islam and Society, 2001)
Islamic modernism contends that muslims should revise their conventional understanding of the requirements of their religion in light of fresh interpretations of authoritative texts. This paper argues that modernism has much more radical impliciations than we might otherwise think. This becomes clear once you distinguish between the arguments that social scientists make about the requirements of a religion from the arguments that participants in a religion should accept. 1 illustrate my views by criticizing the somewhat conservative position of one prominent klamic modernist, Fazlur Rahman.